Sämmtliche Schriften über Generalbaß, Harmonie-Lehre, und Tonsetzkunst: zum Selbstunterrichte - Albrechtsberger, Johann Georg 1736-1809; Seyfried, Ignaz von 1776-1841 (Vienna Haslinger, 1837)
Johann Georg Albrechtsberger (1736-1809) was an Austrian composer and organist who enjoyed a wide reputation as music theorist, teaching Ludwig van Beethoven, Ignaz von Seyfried, Johann Nepomuk Hummel, Ignaz Moscheles, Anton Reicha, Franz Xaver Wolfgang Mozart, and Josef Weigl. In 1792, he became Kapellmeister of St. Stephen's Cathedral instead of Mozart, who had passed away. Possibly the most valuable service he rendered to music was in his theoretical works. In 1790 he published at Leipzig a treatise on composition, of which a third edition appeared in 1821. An English version of this was published by Novello in 1855. His compositional style derives from the counterpoint of Johann Joseph Fux, who was Kapellmeister at St Stephen's Cathedral from 1713 to 1741. Ignaz von Seyfried (1776-1841), who edited Albrechtsberger's works, was also a keyboard student of Mozart.
Originally published in 1826, see 08A15, H.02.070, and H.02.071
H.02.032: Ex libris Carlo Ferdinand Bischof (stamp)
Systematisch geordnet, mit zahlreichen, aus dessen mündlichen Mittheilungen geschöpften Erläuterungs-Beyspielen, und einer kurzen Anleitung zum Partitur-Spiel, nebst Beschreibung alles bist jetzt gebräuchlichen Instrumente. Mit 556 Notenbeispielen.
Keywords: 18th Century (1701-1800); 19th Century (1801-1900); Method; Music theory; Basso continuo; Harmony; Composing; Self-education; Vienna (Austria)